Complex Odontomes - Two Case Reports - Ud Din, Qiam; Sherani, Ayub Shah (Journal of Postgraduate Medical Institute, 2011)
The term "Odontome" by definition referes to any tumor of odontogenic origin but through usage, it has come to mean a growth in which both the epithelial and the mesenchymal cells exhibit compelte differentation, with the result that functional amelobalsts and odontoblasts form enamel and dentine.